2011
DOI: 10.1590/s0102-695x2011005000116
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity, isolation and identification of active compound from Gaylussacia brasiliensis

Abstract: Gaylussacia brasiliensis (Spreng.) Meissn., Ericaceae, is used in folk medicine for treatment of several infl ammatory processes and as healing agent. The scope of this work was to evaluate the in vitro antiproliferative activity of crude dichloromethane extract (CHD) and to identify the compound(s) responsible for this activity. CHD was evaluated and showed a concentration dependent inhibition on all cells lines. Therefore CHD was submitted to several classical columns chromatography providing the most active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…This is because of the pure substance existed in the isolated compound as compared to the crude extract, which consists of various amounts of active constituents (Colegate & Molyneux 2007). A study from Rodrigues et al (2011) also showed that the isolated compound exhibited stronger cytotoxicity compared to the crude extract due to the presence of other compound involved in antiproliferative activity. Meanwhile, the anti-proliferative activity for normal cell lines, normal fibroblast NIH 3T3 and L929 normal connective cells, were also tested to see whether F11 is toxic towards them.…”
Section: Discussionmentioning
confidence: 93%
“…This is because of the pure substance existed in the isolated compound as compared to the crude extract, which consists of various amounts of active constituents (Colegate & Molyneux 2007). A study from Rodrigues et al (2011) also showed that the isolated compound exhibited stronger cytotoxicity compared to the crude extract due to the presence of other compound involved in antiproliferative activity. Meanwhile, the anti-proliferative activity for normal cell lines, normal fibroblast NIH 3T3 and L929 normal connective cells, were also tested to see whether F11 is toxic towards them.…”
Section: Discussionmentioning
confidence: 93%
“…Further, there could be a possible correlation of receptor and intracellular signalizing with different pharmacological mechanism. 33 In regard to this, Burow et al 34 showed that an increase in concentration of glyceollins, isolated from soy, correlated with a greater suppression of ER signaling resulting to a decrease in proliferation of MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…O Brasil possui uma grande diversidade de espécies vegetais localizadas em diferentes regiões, resultando em ecossistemas diversos como a Floresta Amazônica, a Mata Atlântica, o Cerrado, a Caatinga, o Pantanal e os Pampas. Na busca de novos fármacos anticâncer, o laboratório de cultura de células da Divisão de Farmacologia e Toxicologia do CPQBA/UNICAMP, através de projetos financiados pelo CNPq (630009/95-3), FAPESP (95/09607-5) e verbas obtidas com a prestação de serviços, implantou um teste de atividade antiproliferativa in vitro, baseado no experimento desenvolvido pelo National Cancer Institute (NCI) (Rubinstein et al, 1990;Skehan et al, 1990;Monks et al, 1991), em um painel de dez linhagens tumorais humanas (nove tumores sólidos e uma leucemia) que vem sendo utilizado para triagem da atividade antiproliferativa de amostras obtidas a partir de extratos vegetais e de síntese orgânica (Kohn et al, 2006;Denny et al, 2007;Denny et al, 2008;Sacoman et al, 2008;Spindola et al, 2009;Vendramini-Costa et al, 2010;Longato et al, 2011;Rodrigues et al, 2011).…”
unclassified